How does an augmented reality-based pocket book enhance students' critical thinking skills? - Pratiwi, Hanum; Nugraheni, Nursiwi (Universitas Islam Raden Intan Lampung, INDONESIA, 2024)
Background: Students' low critical thinking skills negatively impact their mathematics learning outcomes. One contributing factor is the insufficient optimization of instructional media.Aim: This study aims to design instructional media, assess its feasibility and practicality, and evaluate the effectiveness of an augmented reality-based pocket book in enhancing the critical thinking skills of fifth-grade students at SDN 01 Bligorejo Doro Pekalongan.Method: The study adopts the Borg & Gall development model and employs a pre-experimental design with a one-group pretest-posttest approach. Data collection techniques include observation, interviews, questionnaires, tests, and documentation. Initial data analysis involves normality tests, while final data analysis uses mean difference tests and N-Gain tests.Results: The findings reveal an improvement in students' critical thinking skills, as indicated by the increase in average test scores from 51.5 to 76.6. The N-Gain analysis result of 0.5052, classified as moderate, provides evidence that the augmented reality-based pocket book is effective in enhancing students' critical thinking skills.Conclusion: The augmented reality-based pocket book proves to be an effective tool for improving students' critical thinking skills, as demonstrated by the significant increase in average test scores and N-Gain values.